Analysis of Ion‐Diffusion‐Induced Interface Degradation in Inverted Perovskite Solar Cells via Restoration of the Ag Electrode. Issue 11 (27th December 2017) - Lee, Hyunho; Lee, Changhee
Abstract: Straightforward evidence for ion‐diffusion‐induced interfacial degradation in inverted perovskite solar cells is presented. Over 1000 h, solar cells inevitably undergo degradation, especially with respect to the current density and fill factor. The Ag electrode is peeled off and re‐evaporated to investigate the effect of the Ag/[6, 6]‐phenyl C71 butyric acid methyl ester (PCBM) interfacial degradation on the photovoltaic performance at days 10 (240 h), 20 (480 h), 30 (720 h), and 40 (960 h). The power conversion efficiency increases after the Ag electrode restoration process. While the current density shows a slightly decreased value, the fill factor and open‐circuit voltage increase for the new electrode devices. The decrease in the activation energy due to the restored Ag electrode induces recovery of the fill factor. The diffused I − ions react with the PCBM molecules, resulting in a quasi n‐doping effect of PCBM. Upon electrode exchange, the reversible interaction between the iodine ions and PCBM causes current density variation. The disorder model for the open‐circuit voltage over a wide range of temperatures explains the open‐circuit voltage increase at every electrode exchange. Finally, the degradation mechanism of the inverted perovskite solar cell over 1000 h is described under the proposed recombination system. Abstract : An interfacial degradation mechanism of inverted perovskite solar cells is proposed. The Ag electrode is peeled off and re‐evaporated to investigate the [6, 6]‐phenyl C71 butyric acid methyl ester/Ag interfacial degradation. Through an electrode restoration process, the degradation sources are eliminated, and the photovoltaic parameter variation is explained in detail.